Influence of Additives on the Yield and Pathogenicity of Conidia Produced by Solid State Cultivation of an Isaria javanica Isolate - Kim, Jeong Jun; Xie, Ling; Han, Ji Hee; Lee, Sang Yeob (Mycobiology, 2014)
Recently, the Q biotype of tobacco whitefly has been recognized as the most hazardous strain of Bemisia tabaci worldwide, because of its increased resistance to some insecticide groups. As an alternative control agent, we selected an Isaria javanica isolate as a candidate for the development of a mycopesticide against the Q biotype of sweet potato whitefly. To select optimal mass production media for solid-state fermentation, we compared the production yield and virulence of conidia between 2 substrates (barley and brown rice), and we also compared the effects of various additives on conidia production and virulence. Barley was a better substrate for conidia production, producing 3.43 × 10(10) conidia/g, compared with 3.05 × 10(10) conidia/g for brown rice. The addition of 2% CaCO3 + 2% CaSO4 to barley significantly increased conidia production. Addition of yeast extract, casein, or gluten also improved conidia production on barley. Gluten addition (3% and 1.32%) to brown rice improved conidia production by 14 and 6 times, respectively, relative to brown rice without additives. Conidia cultivated on barley produced a mortality rate of 62% in the sweet potato whitefly after 4-day treatment, compared with 53% for conidia cultivated on brown rice. The amendment of solid substrate cultivation with additives changed the virulence of the conidia produced; the median lethal time (LT50) was shorter for conidia produced on barley and brown rice with added yeast extract (1.32% and 3%, respectively), KNO3 (0.6% and 1%), or gluten (1.32% and 3%) compared with conidia produced on substrates without additives.